Debugging AJAX in Production. - SCHROCK, ERIC (Communications of the ACM, 2009)
The article discusses efforts to debug, or correct, computer code created with AJAX Web site development technology. The lack of robust error messages as well as native stack traces has presented computer scientists with major challenges related to AJAX development. Topics include Web browsers which have as a central design principle the tolerance of failure, the proliferation of complex AJAX applications which have changed the nature of the JavaScript environment, and software engineers who can debug programs during the development phase.